Legal Responsibility For Negligent Actions Of Nurses In Hospital Which Results In Exchanging Newborn Babies - Vira Komala; Edi Setiadi; Sri Ratna Suminar (Cendekia : Jurnal Hukum, Sosial dan Humaniora, 2024)
The obligation to respect human rights is reflected in the Preamble to the 1945 Constitution, especially Article 28B paragraph (2) of the 1945 Constitution which states that: Every child has the right to survival, growth and development and the right to protection from violence and discrimination. To ensure healthcare measures are by standards and are safe, hospitals need to implement processes that support patient rights as long as patients receive services and care at the hospital and are responsible for protecting patients, especially babies who are at high risk of experiencing forms of discrimination and violence in their lives. To improve patient safety so that patient safety incidents do not occur. The research aimed to determine the hospital's responsibility and the legal consequences for nurses for their negligence which resulted in the exchange of newborn babies. Then the results were obtained that based on the teachings of the Doctrine of vicarious liability, hospitals are responsible for compensating for losses by Article 193 of Law Number 17 of 2023 concerning Health and nurses can be held criminally liable based on Article 277 of the Criminal Code.